Is caregiving by baby boomer women related to the presence of depressive symptoms? Evidence from eight national surveys - Chi Chiao; Yun-Yu Chen (BMC, 2018)
Abstract Background A common hypothesis is that caregiving is deleterious to women's mental health. International studies continue to emphasize the importance of mental health issues for women. Yet only a few researchers have used population-based surveys to explore the association between caregiving and depressive symptomatology in the context of the community, and even less is known about this aspect of Baby Boomer women in a global context. Methods The present study uses eight international surveys covering nineteen nations (N = 15,100) and uses multilevel logistic models to examine possible linkages between caregiving and the likelihood of depressive symptoms among Baby Boomer women, when taking individual-level and country-level social factors into consideration. Results The various analyses found a significant variation in the likelihood of depressive symptoms among these Boomer women across the nations investigated and across both individual-level and country-level characteristics. The significant association of caregiving by women and the likelihood of depressive symptoms is related to their social status in some nations (OR = 1.30; p < 0.001). Boomer women living in countries with high rates of female participation in managerial/professional work (OR = 1.04; p < 0.05) and living in countries where women are often in vulnerable employment (OR = 1.01; p < 0.05) are at greater risk of depressive symptomatology. Conclusions These findings demonstrate that the depressive consequences of caregiving by women are, to some degree, contingent upon social context and structure. Policies aimed at promoting mental health among female Baby Boomers should therefore be context specific.